Progress and prospects of thermo-mechanical energy storage—a critical review. (12th March 2021) - Olympios, Andreas V; McTigue, Joshua D; Farres-Antunez, Pau; Tafone, Alessio; Romagnoli, Alessandro; Li, Yongliang; Ding, Yulong; Steinmann, Wolf-Dieter; Wang, Liang; Chen, Haisheng; Markides, Christos N
Abstract: The share of electricity generated by intermittent renewable energy sources is increasing (now at 26% of global electricity generation) and the requirements of affordable, reliable and secure energy supply designate grid-scale storage as an imperative component of most energy transition pathways. The most widely deployed bulk energy storage solution is pumped-hydro energy storage (PHES), however, this technology is geographically constrained. Alternatively, flow batteries are location independent and have higher energy densities than PHES, but remain associated with high costs and short lifetimes, which highlights the importance of developing and utilizing additional larger-scale, longer-duration and long-lifetime energy storage alternatives. In this paper, we review a class of promising bulk energy storage technologies based on thermo-mechanical principles, which includes: compressed-air energy storage, liquid-air energy storage and pumped-thermal electricity storage. The thermodynamic principles upon which these thermo-mechanical energy storage (TMES) technologies are based are discussed and a synopsis of recent progress in their development is presented, assessing their ability to provide reliable and cost-effective solutions. The current performance and future prospects of TMES systems are examined within a unified framework and a thermo-economic analysis is conducted to explore their competitiveness relative to each other as well as when compared to PHES and battery systems. This includes carefully selected thermodynamic and economic methodologies for estimating the component costs of each configuration in order to provide a detailed and fair comparison at various system sizes. The analysis reveals that the technical and economic characteristics of TMES systems are such that, especially at higher discharge power ratings and longer discharge durations, they can offer promising performance (round-trip efficiencies higher than 60%) along with long lifetimes (>30 years), low specific costs (often below 100 kWh −1 ), low ecological footprints and unique sector-coupling features compared to other storage options. TMES systems have significant potential for further progress and the thermo-economic comparisons in this paper can be used as a benchmark for their future evolution.